Contagious Terror: Violence, Haunting and the Work of Refugee Protection - Masoumi, Azar (Studies in social justice, 2021)
This article argues that contrary to its humanitarian semblance, state-controlled refugee protection is a project of substantial violence, and that the violence of refugee protection is continuously disseminated through and across a wide range of unlikely actors and institutions. Drawing on Avery Gordon (2008) and Franz Fanon (1965), I show that the violence of refugee protection makes itself known in its haunting effects on those who come in contact with it in various capacities: those who carry through the work of refugee protection, such as refugee claim decision makers, lawyers and support workers, are plagued by psychological ailments that manifest in periodical burnouts, anxiety, melancholy, alcohol abuse, and unrelenting moral and emotional dilemmas. These ailments reveal the violence of refugee protection not just in relation to refugees, who are often construed as the exclusive subjects of violence, but also towards non-refugees who come into contact with “protection” work.